Role and Function of Lema Treasure Development At KBBI - Sujarno Sujarno; Muhammad Ridwan; Ichtiar Telaumbanua (Universitas Negeri Semarang, 2024)
One indicator of language dynamics is changes in the language itself. One of them is a change in the number of items and vocabulary. Looking at this survey data, we see an increase in the number of participants. This development was marked by changes in the number of participants from KBBI I to KBBI II, from KBBI II to KBBI III, and from KBBI III to KBBI IV. Dictionary entries need to be expanded. Perhaps, there were no special entries in earlier dictionaries, but as development progressed, these entries appeared in later editions of dictionaries. Or vice versa: the previous edition had a certain entry, but that entry is not in the next edition. Therefore, there are several options to change the existence of an entry in KBBI. Dictionaries as lexicographic products are often used in different versions in practice. An ideal dictionary always refers to a language system. It cannot be denied that Indonesian as a national and national language has the ability to become the language of modern science and technology in nation building. The development of various scientific and technological languages must be carried out sparingly and carefully, because it requires clear responses from listeners and readers. The rules of syntax and language formation as well as areas of substitution must be easy to understand. Combined with economical use of language, precision and clarity of syntax, and the elimination of personal elements, it is possible to create a common diversity in science and technology. For example, the absorption of words and terms actually occurs more easily and evenly. The words authentic, validating, validating, and authentic come from the word valid and are synonyms for the words valid, validating, validating, and legitimate.